Role conflict and ambiguity among physicians and nurses in the public health care sector in Crete - Rovithis, Michael; Linardakis, Manolis; Rikos, Nikolaos; Merkouris, Anastasios (My University, 2017)
OBJECTIVE To identify role conflict and role ambiguity in the public health care facilities in Crete, as perceived by physicians and nurses. METHOD A descriptive comparative study was conducted in the 5 public general hospitals, one university hospital and 7 of the 14 health centers in Crete, randomly selected. A sample of 75 physicians and 81 nurses completed anonymously the Greek version of the Role Ambiguity and Role Conflict Scales. Their responses were analyzed using multivariate methods. RESULTS The total score was 3.20±1.30 for role ambiguity and 4.75±1.19 for role conflict. Women presented a higher mean ambiguity score (r=0.203, p<0.05), as did participants in the younger age group (p<0.001). Nurses presented a higher mean ambiguity score (3.48±0.14) and physicians a higher mean conflict score (4.91±0.16). Analysis by health care level reveals statistically significant difference, with staff in the primary care health centers recording a higher mean ambiguity score (3.29 vs 2.14, p<0.001). A statistically significant difference was also found between physicians and nurses (p<0.001), with nurses presenting a higher mean ambiguity score than physicians (3.48 vs 2.90, p=0.020). CONCLUSIONS Role ambiguity and role conflict in doctors and nurses can lead to lowered health service performance and efficiency. Awareness of the degree of role conflict and role ambiguity among health personnel has implications for future research and efficient management. To reduce role ambiguity and conflict, managers of health care facilities should introduce interdisciplinary projects aimed at improving job satisfaction and providing quality patient-centered care.
Keywords: Health services administration; Nurses; Physicians; Role ambiguity; Role conflict